Checking Concordance between Findings and Diagnoses in Sonographic Reports by a Knowledge-Based Documentation System - Huettig, M; Buscher, G; Puppe, F; Buscher, H.-P (Ultraschall in der Medizin - European Journal of Ultrasound, 2008)
Purpose: Sonographic reports are examiner-dependent and may not always be reliable. We investigated concordance between documented findings and diagnostic conclusions - not the objective correctness of both - with the help of a knowledge-based documentation system. Materials and Methods: The knowledge-based documentation system SonoConsult (SC) is routinely used in the ultrasound unit of a gastroenterological clinic for more than four years. Physicians documented findings with goal directed questionnaires, and diagnostic conclusions with free text. The consistency of documented findings and diagnoses was checked with the help of SC in a two-step process: 1. the diagnoses inferred by SC based on the documented findings were compared to the diagnoses of the physicians stated as free text. 2. In case of discrepancies, a more thorough comparison was performed manually by the medical authors of this study. For judging the practical relevance of discrepancies, diagnostic codes were pre-classified as a) being presumably of higher and lower relevance for the clinician and b) requiring simple or complex inference rules from the findings. Results: In a first series of 250 consecutive cases with 934 diagnoses (3.7 diagnoses per case), 71.1 % showed agreement between diagnoses of the physicians and of SC and were judged as consistent compared to the documented findings. 24.4 % of the diagnoses suggested by the documented findings, however, were not mentioned by the physicians (false negative) and 4.5 % were mentioned by the physicians but not suggested by the documented findings (false positive). From the 24.4 % missing diagnoses, 40 % were pre-classified as being of higher relevance for the clinician. In a second series of 161 consecutive cases with 501 diagnoses (3.1 diagnoses per case), 61.1 % were judged as consistent compared to the documented findings, 36.1 % false negative and 2.8 % false positive. In this study, we differentiated the missing diagnoses due to their inferential complexity: From the 152 complex diagnoses, 44 % were missing, while from the 349 simple diagnoses, 32.7 % were missing. Conclusion: As shown for a sonographic department of a clinic of internal medicine, in sonographic reports, one has to be aware of discrepancies between question-set-based documentations of findings and diagnostic conclusions of the examiners. While a detailed documentation of findings is the basis of quality control, consistency checks between documented findings and diagnostic conclusions, which might be done automatically in an electronic patient record, would considerably improve the quality of the reports.
Keywords: quality assurance; ultrasonography; computer-based diagnosis; expert system